2008
DOI: 10.1152/japplphysiol.01040.2007
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular responsiveness to steady-state changes in end-tidal CO2 during passive heat stress

Abstract: CG. Cerebrovascular responsiveness to steady-state changes in end-tidal CO2 during passive heat stress. J Appl Physiol 104: 976-981, 2008. First published January 24, 2008 doi:10.1152/japplphysiol.01040.2007.-This study tested the hypothesis that passive heat stress alters cerebrovascular responsiveness to steady-state changes in end-tidal CO2 (PETCO 2 ). Nine healthy subjects (4 men and 5 women), each dressed in a water-perfused suit, underwent normoxic hypocapnic hyperventilation (decrease PETCO 2 ϳ20 Torr)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
56
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 40 publications
8
56
2
Order By: Relevance
“…However, their follow-up study showed that MCAV mean did not return to the baseline level during heat stress (internal temperature increased by 1.41C) even when P ET CO 2 was clamped to the preheating. 11,12 In the present study, we also calculated the relationship between changes in P ET CO 2 and changes in ICA and VA blood flows throughout heat stress, but there was no significant relationship. We did not perform any perturbation to change P ET CO 2 in this study.…”
Section: Modified Blood Distribution In Hyperthermic Conditionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, their follow-up study showed that MCAV mean did not return to the baseline level during heat stress (internal temperature increased by 1.41C) even when P ET CO 2 was clamped to the preheating. 11,12 In the present study, we also calculated the relationship between changes in P ET CO 2 and changes in ICA and VA blood flows throughout heat stress, but there was no significant relationship. We did not perform any perturbation to change P ET CO 2 in this study.…”
Section: Modified Blood Distribution In Hyperthermic Conditionmentioning
confidence: 67%
“…3 In addition, it is well known that heat stress modifies distribution of blood flow toward cutaneous circulation while decreasing renal and splanchnic blood flows by enhanced vasoconstriction. 15,19 Maintained or decreased cerebral blood velocity during heat stress has been reported [10][11][12][20][21][22][23] but the mechanism remains unclear. The present study demonstrated that CBF conductance in MCAV mean , ICA, and VA gradually decreased during whole body heating, whereas CVC forehead and ECA conductance increased by 3 times and 2.5 times from the baseline, respectively.…”
Section: Modified Blood Distribution In Hyperthermic Conditionmentioning
confidence: 99%
“…[14][15][16] For these reasons, cerebral CO2 reactivity to hypocapnia (hyperventilation) and hypercapnia (rebreathing) was assessed separately in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using end-tidal carbon dioxide tension (PET CO 2 ) to estimate Pa CO 2 during passive heat stress (i.e., increase in internal temperature ϳ1.2-1.5°C) suggest that heat stress reduces Pa CO 2 ϳ4 -8 mmHg (3,5,15,26). A potential limitation to these studies is the assumption that PET CO 2 is an accurate surrogate for Pa CO 2 , the latter being the physiologically relevant variable.…”
mentioning
confidence: 99%
“…To our knowledge, however, there is no information regarding the relationship of PET CO 2 to Pa CO 2 in individuals with elevated internal temperatures. This information is important because heat stress-induced reductions in Pa CO 2 likely contribute to reductions in cerebral blood flow (3,5,15,26) and ultimately reduced orthostatic tolerance in this thermal condition (4,12,25). Because PET CO 2 is commonly used as an index of Pa CO 2 in heat-stressed individuals (3,5,15,26), it is important to identify the relationship between these variables in this thermal condition.…”
mentioning
confidence: 99%